2008
DOI: 10.1161/hypertensionaha.108.117341
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Olmesartan on Tissue Expression Balance Between Angiotensin II Receptor and Its Inhibitory Binding Molecule

Abstract: Abstract-We previously cloned a novel molecule interacting with angiotensin II (Ang II) type 1 receptor protein (ATRAP) and showed it to be an endogenous inhibitor of Ang II type 1 receptor signaling in cardiovascular cells.In this study, we tested a hypothesis that the balance of tissue expression of ATRAP and Ang II type 1 receptor is regulated in a tissue-specific manner during the development of hypertension and related cardiac hypertrophy. T he renin-angiotensin system has been implicated in the pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“…We observed recently that treatment with an AT 1 R antagonist recovered a constitutive decrease in the ratio of cardiac expression of ATRAP/AT 1 R in spontaneously hypertensive rats, which was accompanied by a decrease in cardiac p38 activity and a suppression of cardiac hypertrophy. 30 Previous studies have shown that increases in cardiac p38 activity through the activation of AT 1 R signaling are profoundly involved in cardiac hypertrophy and the damage incurred in genetic and experimental hypertension models, including spontaneously hypertensive rats and Ang II infusion. 31,32 Because we had hypothesized that cardiac-specific upregulation of the ATRAP/AT 1 R ratio suppresses the cardiac hypertrophy induced by Ang II infusion, we produced the cardiomyocyte-specific ATRAP Tg mice, with a constitutively high expression of cardiac ATRAP and a resultant upregulation of the cardiac ATRAP/AT 1 R ratio, to examine this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…We observed recently that treatment with an AT 1 R antagonist recovered a constitutive decrease in the ratio of cardiac expression of ATRAP/AT 1 R in spontaneously hypertensive rats, which was accompanied by a decrease in cardiac p38 activity and a suppression of cardiac hypertrophy. 30 Previous studies have shown that increases in cardiac p38 activity through the activation of AT 1 R signaling are profoundly involved in cardiac hypertrophy and the damage incurred in genetic and experimental hypertension models, including spontaneously hypertensive rats and Ang II infusion. 31,32 Because we had hypothesized that cardiac-specific upregulation of the ATRAP/AT 1 R ratio suppresses the cardiac hypertrophy induced by Ang II infusion, we produced the cardiomyocyte-specific ATRAP Tg mice, with a constitutively high expression of cardiac ATRAP and a resultant upregulation of the cardiac ATRAP/AT 1 R ratio, to examine this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that there is a tissuespecific regulatory balancing of the expression of ATRAP and AT1R during the development of hypertension in spontaneously hypertensive rats (SHRs) [19]. The activation of ATRAP in transgenic-models in which ATRAP expression was increased beyond baseline promoted Ang II-mediated AT1R internalization and inhibited renal angiotensinogen production and cardiac hypertrophy in response to Ang II stimulation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile RAS blockade during a "critical period" results in prolonged blood pressure-lowering and organ protection that remains for a prolonged time after drug withdrawal (Shigenaga et al, 2008). Reduced angiotensin sensitivity has been attributed as a potential mechanism for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ATRAP was up-regulated in prehypertensively treated SHHF. Because ATRAP has been demonstrated to be an endogenous inhibitor of AT1R signaling in cardiovascular cells (Shigenaga et al, 2008), the upregulation of ATRAP in cardiovascular tissue may add to the therapeutic benefits of the preconditioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation